Edukasi Tentang Deteksi Dini Katarak Pada Nelayan Tradisional Sebagai Upaya untuk Meningkatkan Kualitas Hidup: Deteksi dini katarak, nelayan tradisional - Chabibah, Nur; Rachmawati, Dhian Satya; Faridah, Faridah; Mayasari, Ayu Citra; Anggoro, Sapto Dwi; Prasetya, Taufan Agung (Universitas Muhammadiyah Gresik, 2023)
Cataracts are an eye disease characterized by cloudiness of the lens due to hydration, protein denaturation of the lens, or both. The causes of cataracts are exposure to ultraviolet intensely and for a long time. This condition triggers the occurrence of cataracts, especially in traditional fishermen who work outside buildings and are exposed to sunlight for a long time (12 hours) every day. The aim is to educate the traditional fishing community in Gisik Cemandi Sedati Sidoarjo regarding cataracts, the dangers, how to prevent them, how to treat them, and how to detect cataracts early, it is also to recruit people who are willing to become cadres in examining cataract early detection and educating the community about cataracts. The community service method is carried out by providing education on how to detect cataracts early, followed by a question-and-answer session and discussion. then the cadres are taught how to detect cataracts early and are asked to carry out early detection accompanied by medical personnel. The results of community service found that there was a significant difference in the level of knowledge between before and after being given an education